Melhoria do desempenho ambiental através da avaliação do ciclo de vida na fabricação de porta pallets - Rodrigues, Reinaldo Luan (2016)
This study aimed to propose actions to improve environmental performance through the Life Cycle Assessment in manufacturing steel racks, therefore this research followed the regulatory guidelines of ISO 14040 and 14044 standards. Was used Umberto® NXT Universal v. 7.1 as software for modeling and calculation procedures. ICV database used was Ecoinvent v.3.2. We evaluated the impact of the life cycle of production through Racks recipe method (2008). The midpoint impact categories covered were: climate change, ozone depletion, metal depletion, terrestrial acidification, aquatic eutrophication (freshwater), aquatic eutrophication (marine), human toxicity, photochemical oxidant formation, formation of particulate matter, terrestrial ecotoxicity. The results showed three potential sources of environmental impacts (hotspots): Production of steel coil, steel coil transport and refined vegetable oil for steel lubrication. Hotspots were analyzed sensitively and in different scenarios in order to verify the effectiveness in reducing the potential impacts observed. Proposals for environmental performance improvements realized the following actions: reducing consumption of steel coils, minimizing the distance from suppliers and the amount of freight and reduction in vegetable oil consumption. Thus, this study provides grants for research, and assists in the formulation of proposals for improvements in the environmental performance of products and processes in general.